Development of A Problem-Based Learning-Based Heat Student Worksheet to Enhance Senior High School Students’ Creative Thinking Skills - Muliyanti Muliyanti; Suyidno Suyidno; Saiyidah Mahtari (Jurnal Ilmiah Pendidikan Fisika, 2026)
Creative thinking is a crucial 21st-century skill that must be developed through classroom learning. However, in practice, physics learning is still largely dominated by conventional approaches, resulting in suboptimal stimulation of this skill. This study aims to determine the effectiveness of a problem-based learning (PBL)-based student worksheet on the topic of heat in improving senior high school students’ creative thinking skills. This study employed a research and development method using the 4D model. The product was developed based on the PBL syntax and creative thinking indicators, namely fluency, flexibility, and originality. The trial subjects consisted of 27 grade XI students. The instruments used included validation sheets, lesson implementation observation sheets, and pre-test and post-test for creative thinking skills. The validation results showed that the student worksheet belongs to the very valid category, with an average score of 3.78 and high reliability. The practicality results indicated that the student worksheet is highly practical to use, with an average implementation score of 3.65. The effectiveness of the student worksheet was demonstrated by an N-gain score of 0.45 for creative thinking skills, which falls into the moderate category. Therefore, the developed PBL-based heat student worksheet is declared effective in enhancing students’ creative thinking skills in physics learning. This student worksheet is feasible for use as an innovative teaching instrument that promotes active engagement and contextual problem-solving.